Metabolite Characteristics Analysis of Siliques and Effects of Lights on the Accumulation of Glucosinolates in Siliques of Rapeseed - Kamal, Farah; Shen, Shulin; Hu, Ran; Zhang, Qianwei; Yin, Nengwen; Ma, Yifang; Jiang, Yuxiang; Xu, Xinfu; Li, Jiana; Lu, Kun; Qu, Cunmin (Frontiers in Plant Science, 2022)
Glucosinolates (GSLs) are naturally occurring secondary metabolites found in Brassicaceae family, which mainly synthesize in the siliques with a wide range of functions. In this study, we investigated the effects of lights on metabolites in siliques of rapeseed through UPLC-HESI-MS/MS. A total of 249 metabolites, including 29 phenolic acids, 38 flavonoids, 22 glucosinolates, 93 uncalculated and 67 unknown compounds, were identified in siliques of rapeseed. Meanwhile, 62 metabolites showed significant differences after shading treatment, which were mainly GSLs and unknown compounds. Interestingly, the amounts of 10 GSLs had high accumulation levels in siliques, while the expression levels of their corresponding biosynthetic genes (AOP, GSL-OH, IGMT and ST5a) were obviously reduced after shading treatment. Further evidences showed that the amounts of GSLs were significantly reduced in seeds, in accordance with the expression profiles of transporter genes (BnaGTRs). Our findings indicated that lights could affect the accumulation and transportation of GSLs from siliques to seeds in rapeseed. Therefore, this work facilitates a better understanding of metabolic characteristics of siliques, and provides the insight into the importance of light for GSLs accumulation and transportation in siliques and seeds of rapeseed.